AKIBAT HUKUM ANGGOTA YANG WANPRESTASI DALAM PERJANJIAN SIMPAN PINJAM ANTARA ANGGOTA DENGAN KOPERASI DI KOPERASI SIMPAN PINJAM CU PANCUR KASIH TEMPAT PELAYANAN 12 SUNGAI DURIAN KUBU RAYA - RUIS RIO NUSANTO NIM. A1011191094 (Fakultas Hukum Universitas Tanjungpura, 2023)
Abstract Cooperatives have an important role to conduct joint efforts from people who generally have very limited economic capabilities, in order to meet common needs. The Savings and Loans Cooperative of CU Pancur Kasih TP 12 Sungai Durian has a principal deposit (minimum) of Rp. 50,000 and a mandatory deposit of Rp. 10,000. Loans are a maximum of 4 times deposits that are paid in installments of a maximum of 10 times. The purpose of becoming a member of the Savings and Loans Cooperative of CU Pancur Kasih TP 12 Sungai Durian is to apply for a business capital loan. An agreement does not rule out the possibility that if one party is negligent in carrying out obligations as agreed, the negligent party can be said to be in default or default. Therefore, every agreement always has a path to overcome the occurrence of default. This thesis contains a formulation of the problem